Rate of Return on Education in Thailand 4.0: อัตราผลตอบแทนการศึกษาในยุคไทยแลนด์ 4.0 - Plubplueng, Thitima (Journal of Applied Economics and Management Strategy, 2019)
ทคัดย่อ บทความนี้สร้างแรงจูงใจให้ผู้ปกครองตระหนักถึงความคุ้มค่าของการลงทุนทางการศึกษาในยุคไทยแลนด์ 4.0 โดยมีวัตถุประสงค์เพื่อคำนวณอัตราผลตอบแทนทางการศึกษาด้วยวิธีส่วนลด (Elaborated Method) ระหว่างการสำเร็จมัธยมศึกษาตอนต้น (ภาคบังคับ) กับการสำเร็จมัธยมศึกษาตอนปลายสายอาชีวศึกษาและสายสามัญ กลุ่มตัวอย่างเป็นแรงงานหนุ่มสาวมีอายุระหว่าง 15-45 ปี โดยใช้ข้อมูลจากการสำรวจแรงงานและการมีงานทำ (Labor Force Survey) สำนักงานสถิติแห่งชาติปี พ.ศ. 2558 พบว่า แรงงานชายและหญิงที่จบ ม.3 และตัดสินใจศึกษาต่อ ม.6 จะมีอัตราผลตอบแทนภายในของการลงทุนการศึกษาลดลงร้อยละ 5.5 และ 3.5 ตามลำดับ และแรงงานชายและหญิงที่จบ ม.3 และตัดสินใจศึกษาต่อ ปวช.3 จะมีอัตราผลตอบแทนเพิ่มขึ้นร้อยละ 9.5 และ 7.5 ตามลำดับ ดังนั้นพ่อแม่ควรตัดสินใจให้บุตรศึกษาต่อสายอาชีวศึกษา (ปวช.) จะคุ้มค่ามากกว่าสายสามัญ (ม.6) สำหรับสถาบันอาชีวศึกษาควรเพิ่มสัดส่วนผู้เรียนอาชีวศึกษาและผลิตแรงงานสอดคล้องกับความต้องการสถานประกอบการและนโยบายไทยแลนด์ 4.0 คำสำคัญ: อัตราผลตอบแทนทางการศึกษา อาชีวศึกษา สามัญศึกษา ไทยแลนด์ 4.0 ABSTRACT This article motivates parents to realize the value of educational investment in the Thai era. 4.0. The purpose of this study was to determine the rate of return on education calculated using the elaborated method comparing 1) the completion of junior high school (compulsory), 2) the completion of senior high school in vocational courses, and 3) the completion of senior high school in the curriculum courses. The sampling was young workers aged 15 to 45 years using data from the labor force survey. The National Statistical Office in Thailand in 2015 found that the male and female workers that decide to study further in senior high school will have a drop of 5.5 percent and 3.5 percent in the internal rate of return respectively in educational investment, and male and female workers that decide to study further for a vocational degree will have an increase of 9.5 percent and 7.5 percent in the rate of return respectively. Therefore, parents should decide to have their children study vocational education (vocational certificate), which is more rewarding than curriculum courses (high school certificate). For vocational institutions, the proportion of vocational students and labor production should be in line with the requirements of business and Thailand’s 4.0 policy. Keywords: Rate of Return on Education, Vocational Education, General Education, Thailand 4.0